PENGIRIMAN SMS DENGAN AT COMMAND MENGGUNAKAN HANDPHONE GSM HT SERI G20 - Suharnawi Suharnawi Suharnawi (Semantik, 2011)
Handphone is a communication tool that many community-owned. Ease of use of communication tools makes the users can communicate anytime and anywhere, provided the availability of good network. HP has a small form factor makes the owners like to take them where they are located. With these considerations, the presentation of information more quickly will certainly arrive at the destination. Various information in the form of SMS can be sent by one by one to the desired destination, or may be sent to multiple numbers simultaneously destination . SMS service is not just to provide information to the destination but also to accept. This capability is of course, can be utilized for the provision of services that provide information to the needy in accordance with the request. The ability of computers have been equipped to make access to communications with HP equipment. HP Computers can control whether to accept / read incoming SMS, perform as if the data on demand, and gives information / send SMS. Taking advantage of available commands at the computer, the process can be done.Keywords: SMS, handphone, computer, information